THE IMPLEMENTATION OF CAROUSEL ACTIVITY IN TEACHING ENGLISH FOR SPECIFIC PURPOSE TOWARD LAW STUDENTS OF UNMAS DENPASAR - Dewa Ayu Ari Wiryadi Joni (SPHOTA: Jurnal Linguistik dan Sastra, 2015)
Abstract This study aimed at implementing carousel activity as a teaching technique in helping law students of Unmas Denpasar to speak English. These 30 students were chosen because they had difficulties in speaking English. It was conducted using classroom action research design in two cycles with four interconnected sessions. The data were collected through instrumentation; pre-test, post-tests, questionnaire and teacher’s diary. The tests were done orally using speaking rubric; the questionnaires were in the form of multiple choice test item using likert’s scale; teacher’s diary was designed using observation sheet. It was found that the students’ speaking skill had adequately improved; and their behavior, attitude and motivation towards the instruction processes were fairly positive. This study provides the evidence of teaching English for specific purpose using carousel activity. Key words: carousel activity, speaking, law students.